Cellulose triacetate doped with ionic liquids for membrane gas separation. (20th April 2016) - Lam, Benjamin; Wei, Min; Zhu, Lingxiang; Luo, Shuangjiang; Guo, Ruilan; Morisato, Atsushi; Alexandridis, Paschalis; Lin, Haiqing
Abstract: Cellulose triacetate (CTA) is a workhorse polymeric membrane material for industrial CO2 /CH4 separation. This study investigates the doping of CTA with ionic liquids (ILs) to reduce the crystallinity of the CTA and enhance its affinity with CO2, thus increasing CO2 permeability and CO2 /light gas selectivity. CTA films doped with 1-ethyl-3-methylimidazolium tetrafluoroborate ([emim][BF4 ]) and 1-ethyl-3-methylimidazolium dicyanamide ([emim][dca]) were prepared; and the effect of IL loading on properties of the CTA, such as crystallinity, density, degradation temperature, glass transition temperature, and gas transport properties, were determined. The IL doping reduces the glass transition temperature and degree of crystallinity of CTA, increasing gas diffusivity and permeability. The IL doping also increases CO2 /CH4 solubility selectivity and CO2 /N2 permeability selectivity, due to the affinity of these ILs with CO2, compared to light gases such as CH4 and N2 . This study demonstrates a promising route in manipulating the morphology and gas transport properties of semi-crystalline polymers by doping with ILs. Graphical abstract: Highlights: Cellulose triacetate is doped with ionic liquids of [emim][BF4] and [emim][dca]. IL doping decreases CTA crystallinity and Tg, and increases CO2 permeability. IL doping increases solubility and permeability selectivity for CO2 /CH4 and CO2 /N2 .